Systemic risk of the Philippines application of the SRISK risk measure to top Philippine banks - Gaborni, Michael James C.
The paper applies the SRISK measure of systemic risk constructed by Brownlees and Engle (2017), to the Philippines. SRISK estimates the expected capital shortfall of a firm in the event of a systemic crisis. Capital shortfall is an indicator of firm- and of systemic riskiness as it reflects the excessiveness of credit growth which has been the main cause and precursor of financial crisis. Studies in other countries have used the SRISK to measure the riskiness of their financial systems and the risk contribution of firms. Replicating past research, the paper measures the SRISK of top 8 universal banks in the Philippines from the GFC period beginning 2007 up to the near-present 2019, ranks them according to this measure, and pins the factors explaining the results. Results show an increasing SRISK across the sample and at the systemic level, and point to the build-up of bank debt as the main factor behind this trend. The findings may help regulators in constructing macroprudential policy to mitigate the rising systemic risk in the country and in adopting the best quantitative tools for this purpose.